If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 70 = 10(3t + -2) Reorder the terms: 70 = 10(-2 + 3t) 70 = (-2 * 10 + 3t * 10) 70 = (-20 + 30t) Solving 70 = -20 + 30t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-30t' to each side of the equation. 70 + -30t = -20 + 30t + -30t Combine like terms: 30t + -30t = 0 70 + -30t = -20 + 0 70 + -30t = -20 Add '-70' to each side of the equation. 70 + -70 + -30t = -20 + -70 Combine like terms: 70 + -70 = 0 0 + -30t = -20 + -70 -30t = -20 + -70 Combine like terms: -20 + -70 = -90 -30t = -90 Divide each side by '-30'. t = 3 Simplifying t = 3
| 3.9m-3-3.9m-9= | | 27-10x=x-33 | | 3(5)+1= | | 27-10x=-33 | | 8x^2-26x+21=0 | | 9(3)(3)-2= | | 3(2)(3)-5(2)= | | 11m-(6m-5)=5 | | 3/5(p-3)=-4 | | 5+2a/3=5/11 | | -6(-3u+4)-4u=2(u-3)-4 | | 16x^2-24x+1=0 | | 6x-4=2(x-4) | | 15-2k=5(4k+3)+k | | 120=5x | | 9x+6-4x/2=8 | | x/3-1/2=3/4 | | =5x-6 | | 124x=15 | | j/6-9=5/18 | | 12/15=28/35 | | 68-12=4x | | 6v-5/8=7/8 | | -3(1+x)-6x=7-4x | | a/7+5/7=2/7 | | 7(y-1)=2(3y+1) | | x-2(2x+10)=12 | | 3x+7/2=8 | | A=2(l+1) | | 1/2(12n-8)=26 | | A=x+y | | -21+x=5+4(1+4x) |